2007
DOI: 10.1007/s00586-007-0335-9
|View full text |Cite
|
Sign up to set email alerts
|

Non-genetic expression of adolescent idiopathic scoliosis: a case report and review of the literature

Abstract: Treating children with idiopathic scoliosis can amaze someone at the many different ways in which the deformity can present. Most authors state that genetics stipulates the course of adolescent idiopathic scoliosis. This is mainly based on the high concordance in monozygotic twins. However, there is indication that environmental factors have influences on adolescent idiopathic scoliosis. This is the first report in which a monozygotic twin pair is described concordant for idiopathic scoliosis but with differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 28 publications
0
13
0
3
Order By: Relevance
“…It is indicated that the incidence of scoliosis in first-degree relatives is significantly higher than in the general population. In addition, SI concordance (meaning that both twins have this pathology) in monozygotic twins is higher in comparison to dizygotic twins [3], which further indicates the influence of genetic factors [3][4][5][6]. Thus, it justifies studies undertaken to estimate the relationship of genetic factors with scoliosis susceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…It is indicated that the incidence of scoliosis in first-degree relatives is significantly higher than in the general population. In addition, SI concordance (meaning that both twins have this pathology) in monozygotic twins is higher in comparison to dizygotic twins [3], which further indicates the influence of genetic factors [3][4][5][6]. Thus, it justifies studies undertaken to estimate the relationship of genetic factors with scoliosis susceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…Multifactorial nature of idiopathic scoliosis is well illustrated by the genetic model proposed by Cheng et al with a set of genes responsible for the initiation and another set involved in the curve progression [4]. These genes could act separately or interact and probably be influenced by diverse environmental and possibly epigenetic factors [4,5,34]. In this context IS could be a systemic molecular disorder or disorders reflected at least in part by local processes affecting musculoskeletal structures of the spine during periods of intensive growth and development.…”
Section: Discussionmentioning
confidence: 99%
“…The enormous amount of data relating etiology of idiopathic scoliosis to structural elements of the spine, neuromuscular, proprioceptive, hormonal and biomechanical factors together with undisputable association with gender, growth and genetics indicates the multifactorial nature of this condition [1-3]. In accordance with the multifactorial nature of idiopathic scolioses is the concept of probably multiple genes predisposing to the deformity that could interplay with disease-modifier genes under the influence of diverse environmental and possibly epigenetic factors [4,5]. It seems generally accepted that girls with idiopathic scoliosis present a tendency to be taller and more slender than their peers [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…This is important because it highlights the impact of factors other than genetic make-up in developing scoliosis and has spawned the concept of epigenetics where factors other than genetics are considered to be major contributing factors (Grivas et al, 2002a(Grivas et al, , 2002b(Grivas et al, , 2006(Grivas et al, , 2007(Grivas et al, , 2008a(Grivas et al, , 2008b(Grivas et al, , 2009(Grivas et al, , 2001. Factors that might be considered must certainly include environmental conditions and their influence on spinal curve development and might present alternative treatment strategies (Hermus et al, 2007). This probability of ~70% also shows the limitations of genetic screening being successful in this search because individuals with identical DNA can have diverse degrees of scoliosis, sometimes ranging from severe in one twin to none in the other.…”
Section: The Promise Of Genetic Studiesmentioning
confidence: 99%